Global redistribution of income - Bourguignon, François, 1945- 1945- (Policy research working paper, 2006)
"The actual distribution of world income across countries is extremely unequal, much higher than the within country inequality faced by most countries. The question studied in this paper is: How do international policies on aid, trade, and factor movements affect the international distribution of income? To begin to answer this question, the authors calculate the impact by decile of the actual level of aid flows and the effect on potential income of merchandise trade restrictions by high-income countries. They find that aid's distributional impact is equality enhancing. While it is extremely small in terms of changes in standard inequality measures, it is of some importance for the lowest decile of the world's income distribution. The authors also find that some of this impact is counteracted by lost potential income in the lower deciles from merchandise trade barriers imposed by high-income countries. In brief, there is a contradiction in international policies where aid's equality-enhancing effect is somewhat offset by protectionism. They also discuss some of the analytical difficulties with extending this analysis of redistribution to other forms of international factor flows-more specifically, migrant worker and profit remittances. The analysis presented is partial and static and ignores within country distribution. As such, the authors suggest that future research should explore the distributional consequences of the broader general equilibrium effects, dynamic effects, and externalities associated with aid, trade, and factor flows. Future research should also analyze the within country distributional impacts of international policies. "--World Bank web site